Analisis Makna Tataran Semiotik Charles Sanders Pierce: Relasi Trikotomi (Ikon, Indeks dan Simbol) pada Puisi Kaum Wikwik Karya S. A.W. Notodihardjo - Wahyuni, Sri; Ridwan, Muhammad Hasbullah (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze the Meaning of Charles Sanders Pierce's Semiotic State: Trichotomy Relations (Icons, Identities and Symbols) in Wikwik Poems by S. A.W. Notodihardjo. Semiotics, as the study of signs and symbols, provides a strong theoretical foundation in analyzing how language in poetry functions in constructing meaning. This research uses qualitative descriptive data that refers to the real reality in the form of writing, then analyzed and reinterpreted. The method used in this study is data collection with the author's direct interview technique, text analysis and interpretation of the results. The results of the research found were: (1) The icon aspect was found as many as 7 icons from some of the perverse lines, (2) The index aspect was found as many as 6 indexes from each verse line, (3) The symbol aspect was found as many as 5 symbols from some of the perverse lines.